The influence of selected variables on the level of cyberbullying at the high school students - Kubiatko, Milan; Balátová, Kristýna; Tomčalová, Nikola (e-Pedagogium, 2021)
Cyberbullying is one of the phenomena that are an inseparable part of the education process nowadays. The aim of the research was to determine the level of cyberbullying related to the upper-secondary level students, the impact of variables such as loneliness, gender, school grade, residence, number of siblings, present status, mother and father education. The survey sample was made up of 269 high school students. A questionnaire with Likert-type items was used as a research tool. The results showed an important influence of the selected variables and their impact is discussed at the end of the study. The implications to practice were presented as well.
Keywords: quantitative approach; cyberbullying; influence of selected variables; upper-secondary level students; high school students.